Highly tough, freezing-tolerant, healable and thermoplastic starch/poly(vinyl alcohol) organohydrogels for flexible electronic devices. Issue 34 (19th August 2021) - Lu, Jing; Gu, Jianfeng; Hu, Oudong; Fu, Yunhan; Ye, Dezhan; Zhang, Xi; Zheng, Ying; Hou, Linxi; Liu, Huiyong; Jiang, Xiancai
Abstract : Herein, the preparation of a highly tough, freezing-tolerant, healable and thermoplastic starch/poly(vinyl alcohol) organohydrogel for flexible electronic devices is presented. Abstract : Conductive hydrogels have found large application prospects in the fabrication of flexible multifunctional electronic devices for future-generation wearable human–machine interactions. However, their inferior mechanical strength, low-temperature resistance, and non-recyclability, resulting in the waste of resources, severely hinder their application. Thus, starch bio-based hydrogels have attracted significant attention. Starch is the most abundantly available biodegradable biopolymer. However, starch bio-based hydrogels usually show low toughness, high brittleness and low anti-freezing properties. Thus, to address these issues, herein, glycerol and CaCl2 were concurrently introduced to a starch/poly(vinyl alcohol) (PVA) hydrogel to improve its mechanical, thermal and conductive properties. The effect of glycerol and CaCl2 on the crystallinity, mechanical, thermal and conductive properties was revealed by X-ray diffraction, tensile testing, differential scanning calorimetry, and electrochemical impedance spectroscopy. The thermoplasticity and healing properties of the starch/PVA/glycerol/CaCl2 organohydrogel was also evaluated. Due to the role of glycerol and CaCl2, the compatibility between starch and PVA improved, and thus the as-prepared organohydrogels showed favorable mechanical flexibility and demonstrated anti-freezing ability and long-term stability at ambient temperature. Besides, the abundant hydrogen bonds formed among PVA, starch, glycerol and water endowed the organohydrogels with high stretchability (>790%) and good thermoplasticity. Finally, based on the starch/PVA/glycerol/CaCl2 organohydrogel, a flexible all-solid-state supercapacitor and strain sensor were assembled and their performances were measured. The supercapacitor displayed an areal specific capacitance of 107.2 mF cm −2 at 1 mA cm −2 . Moreover, the strain sensor demonstrated high sensitivity (gauge factor of 3.422) and could be directly attached to the human body to detect motion.